PENGARUH PENGAWASAN KEUANGAN DAERAH, AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris pada Pemerintah Daerah Kabupaten Solok) - Yuqa Diana Khairi; Wahyu Meiranto (Diponegoro Journal of Accounting, 2021)
This study aims to identify the effect of Regional Financial Supervision, Accountability and the influence of Regional Financial Management Transparency on the Regional Government Performance Solok Regency. The sample used in this study was 110 respondents from echelon III and IV employees at 5 agencies and 17 regional apparatus organization offices (OPD) of Solok Regency. The data used are primary data with data collection methods, namely the distribution of questionnaires/questionnaires directly measured by a Likert scale. The data used are primary data with data collection methods, namely the distribution of questionnaires/questionnaires directly measured by a Likert scale. Hypothesis testing is done by using multiple linear regression analysis method using IBM SPSS 25 software. The results of this study indicate that the Regional Financial Supervision, Accountability and the Transparency of Regional Financial Management has a positive effect on The Performance of the Solok Regency Government.